QUAIL BREEDER’S PRODUCTION PERFORMANCE IN RESPONSE TO SELECTION FOR HIGHER THREE WEEKS BODY WEIGHT - J. Hussain; M. Akram; K. Javed; H. A. Ahmad; A. Mahmud; S. Mehmood; S. Ahmad; F. Ahmad; A. S. Jatoi; Y. Abbas; F. Hussnain (Journal of Animal and Plant Sciences, 2016)
The present study was executed to compare breeder performance parameters (feed intake, Age at 1st egg, egg weight, hen day & hen house production %, FCR /kg and/dozen eggs) in mass selected (MS), pedigree based selected (PS) and random bred controls (RBC), in three consecutive generations of Japanese quail. In generation1 (G1), 11000 quail chicks were randomly distributed into 22 sub-groups. After 3 weeks, birds were weighed and sexed; the higher body weight birds were selected as the parents of next generation. Out of 22 groups, first group was maintained with fully pedigree record, in second group birds were picked randomly without following any selection procedure, rest 20 groups were subjected to mass selection. Pedigree selection significantly improved egg weight, egg mass and FCR/ kg egg mass in higher body weight selected birds with the advancement in generations. Hence, it can be concluded that short term selection for higher 3-week body weight in quails exhibited little or no deterioration, rather improved subsequent production performance with the advancement of generations.
Keywords: Selection; Japanese quail; age at 1st egg; egg production performance; Egg mass; FCR/kg egg mass